Development and Evaluation of Rutin-HPβCD Inclusion Complex Based Mouth Dissolving Tablets - Hitendra S Mahajan; Krishna G Bhalkar (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2017)
The objective of the present study was to explore inclusion complex of Rutin to improve the aqueous solubility and dissolution rate along with rapid mouth dissolving tablets for oral drug delivery. Rutin is a BCS class II drug having low aqueous solubility and therefore low oral bioavailability. In the present study, inclusion complex of rutin with hydroxypropyl-b-cyclodextrin were prepared by kneading method. Inclusion complex were characterized by 1H NMR, X-ray diffractometry (XRD), differential scanning calorimetry (DSC) studies, and Fourier transform infrared spectroscopy and evaluated for phase solubility study, saturation solubility and in vitro dissolution studies of plain drug (Rutin) and HPβCD inclusion complex. DSC and XRD study demonstrated that there was a significant decrease in crystallinity of pure drug present in inclusion complex (Rutin- HPβCD), which resulted in an increased dissolution rate of Rutin and 1H NMR studies strongly, confirmed that the inclusion complex has formed. The formulation so prepared were characterized for its disintegration, wetting properties, dissolution studies etc. Inclusion complexation results in improvement in solubility and dissolution rate. The inclusion complexation would be suitable method for dissolution and bioavailability enhancement of Rutin. Inclusion complex prepared by kneading method is promising approach for enhancing dissolution rate which increases oral bioavailability of poorly water soluble drugs.